2009
DOI: 10.1159/000236409
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor-β mRNA Is Associated with Adverse Outcome in Patients with Breast Cancer

Abstract: Background/Aims: Estrogen receptor (ER) is the prototype therapy predictive marker in oncology. The ER is now known to exist in two main forms with similar overall structure: ER-α and ER-β. Both forms may be expressed in breast cancer. The aim of this study was to examine breast cancer outcome in relation to expression of ER-β. Methods: In this investigation, we measured the expression of ER-α protein and ER-β mRNA in 121 extracts of invasive breast cancer. Association of expression with clinical outcome was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Further, we revealed an independent association of high ER-beta-mRNA levels, quantitatively measured using the QuantiGene2.0 assay, with poor disease-free survival in ER-alpha positive and endocrine therapy treated settings. ER-beta mRNA appeared to indicate a poor response to treatment [23-25], which was supported by the correlation of ER-beta mRNA with tumor grade and the up-regulation of some subtypes of ER-beta during breast cancer tumorigenesis and tumor progression [26]; whereas positive ER-beta protein (even though we did not revealed the predictive value in this study) was thought to indicate a favorable response to anti-estrogen treatment [27,28]. Although there is no clear explanation for these differences, the more dominant regulation of ER-beta protein by a degradation process, in addition to regulation at a transcription level, was suggested [17].…”
Section: Discussionmentioning
confidence: 99%
“…Further, we revealed an independent association of high ER-beta-mRNA levels, quantitatively measured using the QuantiGene2.0 assay, with poor disease-free survival in ER-alpha positive and endocrine therapy treated settings. ER-beta mRNA appeared to indicate a poor response to treatment [23-25], which was supported by the correlation of ER-beta mRNA with tumor grade and the up-regulation of some subtypes of ER-beta during breast cancer tumorigenesis and tumor progression [26]; whereas positive ER-beta protein (even though we did not revealed the predictive value in this study) was thought to indicate a favorable response to anti-estrogen treatment [27,28]. Although there is no clear explanation for these differences, the more dominant regulation of ER-beta protein by a degradation process, in addition to regulation at a transcription level, was suggested [17].…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported that increased expression of ERβ predicts a more favorable response to tamoxifen therapy [22,23,24,25,26,27,28,29,30,31] but other investigators have reported that ERβ expression predicts a poor outcome in patients treated with tamoxifen [32,33]. In regard to AI therapy, one study has reported no correlation between the expression of ERβ and the response to exemestane as primary endocrine therapy in ERα-positive breast cancer [34].…”
Section: Discussionmentioning
confidence: 99%
“…Esslimani-Shaha et al ascribe the progression of the malignancy and tamoxifen resistance to the decreased expression of ERb (Shaaban et al 2003, Esslimani-Sahla et al 2004, Hopp et al 2004. However, there are also studies which show high ERb expression in ductal cancer and in these studies, ERb expression is associated with poor prognosis (Markey et al 2009, Kim et al 2012. The reasons for the reported differences in the contribution of ERb to breast cancer progression will no doubt be explained as more studies are done and the antibodies used become more standardized.…”
Section: ) While Others Have Found That It Ismentioning
confidence: 99%